Framework for Managers' Engagement Enthusiasm with Smart Technologies in the Platform Government - Jafarian, Mohammad Mehdi; Roodsaz, Habib; Seyyed Naghavi, Mir Ali; Koushkie Jahromi, Alireza (Digital Transformation and Administration Innovation, 2025)
The present study was conducted with the aim of developing a framework for managers’ engagement enthusiasm with smart technologies in the context of a platform government. This research is applied in nature, employs a qualitative data collection method, and utilizes a thematic analysis approach as its research execution method. Using the three-step thematic analysis method, the study offers a conceptual framework for understanding the enthusiasm of managerial engagement with smart technologies in the platform government. A total of 15 interviews were conducted, and through analysis and coding of related texts, the descriptive codes derived from the first phase were grouped into related categories. Based on the subject literature and theoretical sensitivity, a total of 231 open/descriptive codes, 159 basic themes, 22 organizing themes, and 8 overarching themes were identified. In the subsequent sections, the framework for managerial engagement enthusiasm with technology in the platform government was presented as a thematic network. The proposed framework in this study identifies the various dimensions that governments must consider in their activities and programs to realize and institutionalize a smart government. The research attempts to provide a comprehensive framework by identifying key dimensions that can serve as the basis for government planning and policymaking.